Weightbearing Versus Nonweightbearing After Meniscus Repair. (September 2015) - VanderHave, Kelly L.; Perkins, Crystal; Le, Michael
Context: Optimal rehabilitation after meniscal repair remains controversial. Objective: To review the current literature on weightbearing status after meniscal repairs and to provide evidence-based recommendations for postoperative rehabilitation. Data Sources: MEDLINE (January 1, 1993 to July 1, 2014) and Embase (January 1, 1993 to July 1, 2014) were queried with use of the terms meniscus OR/AND repair AND rehabilitation . Study Selection: Included studies were those with levels of evidence 1 through 4, with minimum 2 years follow-up and in an English publication. Study Design: Systematic review. Level of Evidence: Level 4. Data Extraction: Demographics and clinical and radiographic outcomes of meniscus repair at a minimum of 2 years follow-up were extracted. Results: Successful clinical outcomes ranged from 70% to 94% with conservative rehabilitation. More recent studies using an accelerated rehabilitation protocol with full weightbearing and early range of motion reported 64% to 96% good results. Conclusion: Outcomes after both conservative (restricted weightbearing) protocols and accelerated rehabilitation (immediate weightbearing) yielded similar good to excellent results; however, lack of similar objective criteria and consistency among surgical techniques and existing studies makes direct comparison difficult.